Response of weeds to the intensification of Kansas No-Till crop rotations with cover cropping - Petrosino, Justin Scott (Kansas State University, 2010)
No-till producers can manage weeds by including cover crops during the fallow phase as part of an integrated weed management plan. Field experiments were conducted between 2007 and 2009 to quantify the influence of cover crops on weed emergence, biomass accumulation, and seed production. Field experiments were established near Garden City, KS with winter wheat or fallow as main plots and cover crop treatments as subplots including five spring- and five fall-sown individual or mixtures of crop species and a no-cover chemical fallow. Separate1-m2 quadrats were seeded with kochia or downy brome at 500 seed/m2. Kochia density was reduced by 75% and biomass reduced by 88% in fall-sown cover crops compared to chemical fallow across growing seasons. Spring-sown cover crop mixtures reduced kochia biomass in 2009 when kochia emergence was delayed. Downy brome biomass decreased exponentially as cover crop biomass increased. A second field experiment was established near Manhattan, KS with soybean, winter wheat, or grain sorghum phases of the rotation as main plots and six cover crop treatments as subplots sown after winter wheat harvest. Paired Palmer amaranth 1-m2 quadrats were seeded with 500 seed/m2 in each cover crop subplot. One quadrat was protected from any herbicide application made to the cover crop or to the grain sorghum. Combining burndown application with high biomass-producing cover crops reduced Palmer amaranth emergence and biomass. Influence of cover crop presence reduced early season Palmer amaranth emergence in the subsequent grain sorghum phase. Optimal seeding rate of forage soybean sown in winter wheat stubble and its impact on Palmer amaranth and downy brome emergence and growth were evaluated in field studies established near Manhattan and Hesston, KS in 2008 and 2009. Soybean was no-till drilled after wheat harvest at five rates ranging from 100,000 to 600,000 seeds/ha. A no-cover chemical fallow treatment was included. Separate 0.5-m2 quadrats were seeded with Palmer amaranth at 100 seed/0.5 m2 or with downy brome at 250 seed/0.5 m2. Three termination methods evaluated were killing frost, glyphosate application, or crop rolling. Palmer amaranth density was not affected by treatments but biomass decreased as soybean seeding rate and crop biomass increased. Downy brome emergence was less with rolled or sprayed termination methods in one site year as timing of termination was optimal. High biomass producing cover crops sown during the fallow phase of a crop rotation reduced weed emergence, density, and biomass accumulation. Cover crops can be part of an integrated weed management plan in Kansas.
Keywords: Cover Crops; Amaranthus palmeri; Kochia scoparia; Sorghum; Soybean; Wheat; Agriculture, Agronomy (0285); Biology, Ecology (0329)